Triboelectric nanogenerator hybrid array driven by multiform natural energies and its applications in self-powered cathodic protection - Sun, WeiXiang; Yang, Di; Luo, Ning; Li, Hao; Wang, DaoAi (Science China. Technological sciences, 2024)
In view of the increasing energy shortage and environmental pollution, the collection of friction charges to achieve the conversion of various natural energies and provide in-situ cathodic protection for metals is a significant challenge. Here, we designed a dual device-structure TENG composite array with the triboelectric layer of linear siloxane-modified polyurethane (PU) coating. This array could achieve a comprehensive collection for multiple forms of nature energy and cathodic protection of metals in multi-weather conditions. For one thing, the wave-mode TENG based on tanker structure could collect wave energy and showed the output performance with a short-circuit current of 15.5 µA. For another hing, the droplet-mode TENG based on arc-shaped surface structure could collect raindrop kinetic energy and showed the output performance with a short-circuit current of 16.3 µA. Notably, the parallel array of wave-mode TENG (W-TENG) and droplet-mode TENG (D-TENG) could simultaneously collect wave energy and raindrop kinetic energy, which showed a short-circuit current of 30.7 µA. Besides, a self-powered a cathodic protection system powered by the dual structure TENG array is assembled and the open-circuit potential drop of the carbon steel connected with the TENG array is about 450 mV. Compared with cathodic protection system powered by single structure TENG, the composite array could provide more effective corrosion resistance for marine equipment in rainy weather. Due to the characteristic for comprehensive collection of nature energy, the anti-corrosion system supplied by TENG parallel array possesses great application potential in the all-weather corrosion protection of metal machinery under complex marine conditions.